Analysis of the Performance of the Garoga District Election Supervisory Committee in Supporting the 2024 Simultaneous Regional Elections - Lusti Hertina Nababan; Adam Adam; Beby Masitho Batubara (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2026)
The 2024 Simultaneous Regional Head Election (Pilkada) is an important moment in the consolidation of local democracy that demands honest, fair, and integrity elections. In this context, the District Election Supervisory Committee (Panwaslu Kecamatan) has a strategic role as the spearhead of supervision at the grassroots level. This study aims to analyze the performance of the Garoga District Panwaslu in supporting the implementation of the 2024 Simultaneous Regional Elections. The research uses a qualitative approach with a descriptive-analytical design. Data were collected through in-depth interviews, observations, and document studies, and then analyzed interactively through data reduction, data presentation, and conclusion drawing. The results of the study show that the performance of the Garoga District Panwaslu, in general, has been in accordance with the institutional mandate, particularly in basic technical competence and administrative compliance. However, the performance of supervision is still dominated by procedural orientation and is not fully substantive and preventive. Limited resources, geographical conditions, and local social dynamics affect the District Panwaslu’s responsiveness, coordination, and adaptability. This research emphasizes the importance of strengthening the performance of the District Panwaslu to be more responsive, collaborative, and adaptive, thereby improving the quality of supervision of the Regional Elections and local democracy.